1998
DOI: 10.1159/000013810
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Patients with Ménière’s Disease Using Otoacoustic Emissions

Abstract: Otoacoustic emissions (OAEs) were studied in patients with Ménière’s disease in order to assess their usefulness for distinguishing between different stages of the disease. An accurate classification of Ménière’s patients is expected to allow optimalization of the treatment for each particular stage. Click-evoked and distortion product OAEs were evaluated in both ears for 70 Ménière’s patients. Based on these measurements, Ménière’s patients can be divided into four different categories. In patients with small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The use of OAEs in the assessment of patients with Meniere's disease has been well documented [11]. In patients with tinnitus, OAEs are not easily detectable or are abnormal at the tinnitus frequency region, even in patients with normal hearing.…”
Section: Discussionmentioning
confidence: 99%
“…The use of OAEs in the assessment of patients with Meniere's disease has been well documented [11]. In patients with tinnitus, OAEs are not easily detectable or are abnormal at the tinnitus frequency region, even in patients with normal hearing.…”
Section: Discussionmentioning
confidence: 99%
“…Using invasive measurements is difficult to perform because of the vulnerability of the human inner ear. The changes in OAE levels in ears with Menière's disease have been proposed as being potentially useful indicators, for clinical monitoring of labyrinth function [29][30][31]. The DPOAE signals provide an original way to estimate the time constant by noninvasive technique.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that OAEs and, in particular, distortion product otoacoustic emissions (DPOAEs), may determine the important information about which cochlear regions have been involved in the irst phase of MD characterized by recurrent hydropic crisis [25,26]. Considering that the acoustic energy has to cross the middle ear structures twice, OAE response may be reduced or even suppressed due to imperfections of the middle ear transmission mechanism.…”
Section: Oaes and MDmentioning
confidence: 99%
“…In this context, one expects that the OAE responses should be atenuated at low or at high frequencies. There are a few reports in the literature showing the exact opposite [36]. In a study by van Hufelen et al [36], MD cases were classiied into 4 groups.…”
Section: Dpoaes and MDmentioning
confidence: 99%
See 1 more Smart Citation